2002
DOI: 10.2337/diacare.25.8.1390
|View full text |Cite
|
Sign up to set email alerts
|

Detection of GAD65-Reactive T-Cells in Type 1 Diabetes by Immunoglobulin-Free ELISPOT Assays

Abstract: OBJECTIVE -To investigate the prevalence of ␤-cell autoantigen-reactive peripheral T-cells in type 1 diabetes, we developed an immunoglobulin-free enzyme-linked immunospot (ELIS-POT) assay and assessed its usefulness for diagnosing this disease. RESEARCH DESIGN AND METHODS-Cellular immune responses to ␤-cell autoantigens were studied both by immunoglobulin-free proliferation assays and ELISPOT assays in 33 patients with type 1 diabetes and 15 patients with type 2 diabetes, compared with 23 healthy control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The ELISPOT assay was performed as previously described [10]. In brief, nitro-cellulose-bottomed 96-well microtitre plates were coated with 15 µg/ml of mouse antihuman IFN-γ monoclonal antibody (mAb; 1-DIK; Mabtech, Stockholm, Sweden) or mouse anti-human IL-4 mAb (IL-4-I; Mabtech AB) in sterile coating buffer (0.1 mol/l carbonatebicarbonate buffer, pH 9.6) overnight at 4°C.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ELISPOT assay was performed as previously described [10]. In brief, nitro-cellulose-bottomed 96-well microtitre plates were coated with 15 µg/ml of mouse antihuman IFN-γ monoclonal antibody (mAb; 1-DIK; Mabtech, Stockholm, Sweden) or mouse anti-human IL-4 mAb (IL-4-I; Mabtech AB) in sterile coating buffer (0.1 mol/l carbonatebicarbonate buffer, pH 9.6) overnight at 4°C.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…In the previous report, six of seven Type 1 diabetic patients with no diabetes-related antibodies also had GAD-reactive T-helper-1 cells [10]. To investigate whether T cell autoimmune responses are involved in fulminant Type 1 diabetes, we evaluated the presence of islet cell antigen-reactive T cells using an ELISPOT assay in fulminant Type 1 diabetic patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We previously developed an immunoglobulin-free ELISPOT assay, which had a low background, and reported that this method could detect GAD-specific T cells in human T1D (10,11). In this report, ELISPOT assay was performed using serial overlapping insulin peptides in Japanese patients with T1D.…”
mentioning
confidence: 99%
“…In fact, the binding of phogrin autoantibodies could be totally blocked if adding ICA512 to sera positive for both ICA512 and phogrin, while the binding of ICA512 antibodies cannot be fully blocked with phogrin (Savola, 2000). IA-2As can be evaluated by radioligand-binding assay and ELISA (Bonifacio et al, 2001;Chen et al, 2005a;Kotani et al, 2002); whereas, RIAs performed much better than ELISAs, as was found for GAD65A assays (Verge et al, 1998).…”
Section: Anti-tyrosin Phosphatase Autoantibodiesmentioning
confidence: 99%